The Influence of Advertising on Consumer Buying Interest of Local Brand Wardah Cosmetics - Ningrum Dwi Vira; Mukhlas Abdulloh Arif (JOSSE: Journal of Social Science and Economics, 2023)
The cosmetics industry is a sector full of competition, where many local and international brands compete with each other to attract the attention of consumers. In the face of this competition, advertising becomes a very important tool for these companies to introduce products and influence consumer perception and buying interest. This study aims to understand the extent to which advertising influences consumers' buying interest in Wardah's cosmetic products in Menganti Village, which is one of the popular local brands in Indonesia. Data was collected with a closed questionnaire instrument with Likert scale. The population in the study was wardah cosmestic consumers in Menganti Village. Purposive sampling technique used. The sample was calculated by the Cochran formula which resulted in 385 respondents. The data is then processed using nonparametric statistical methods, which include linear regression tests, t tests, and R2 tests. The results showed that there was a positive influence on the use of wardah advertising in influencing consumer buying interest in Menganti Village. The amount of influence is shown by the value of the correlation coefficient of 12.6%. This study reinforces the results of existing research that fish has a positive impact on consumer buying interest.